A review of the Nearctic Odontomachus (Hymenoptera: Formicidae: Ponerinae) with a treatment of the males - Macgown, Joe A.; Boudinot, Brendon; Deyrup, Mark; Sorger, D. Magdalena (Zootaxa, 2014)
The ant genus Odontomachus Latreille in the United States is reviewed. Six species are treated: O. brunneus (Patton), O. clarus Roger, O. desertorum Wheeler stat. nov., O. relictus Deyrup and Cover, O. ruginodis M.R. Smith, and O. haematodus (Linnaeus), a new record for North America. The spread of O. haematodus is documented, and its identity is clarified. The genus is diagnosed for species in the Nearctic region for all castes, and worker- and male-based keys are presented. The workers and males of all six species are described and figured, including the first male descriptions for O. haematodus and O. desertorum. This represents the first study of species-level variation in Odontomachus male genitalia, and one of the first of such studies of the Ponerinae for any biogeographic region. A discussion of the utility of the male sex for Odontomachus taxonomy is provided.